2020
DOI: 10.1063/1.5142712
|View full text |Cite
|
Sign up to set email alerts
|

Speed dependence of friction on single-layer and bulk MoS2 measured by atomic force microscopy

Abstract: We perform atomic force microscopy (AFM) experiments on mechanically exfoliated, single-layer and bulk molybdenum disulfide (MoS 2) in order to probe friction forces as a function of sliding speed. The results of the experiments demonstrate that (i) friction forces increase logarithmically with respect to sliding speed, (ii) there is no correlation between the speed dependence of friction and the number of layers of MoS 2 , and (iii) changes in the speed dependence of friction can be attributed to changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
4
13
1
2
Order By: Relevance
“…The PTT model represents, in a simplified way, the setup of an atomic force microscopy (AFM) experiment, in which a cantilever with a small tip having a radius typically on the order of tens of nanometers is pulled across a periodic crystal surface. Many AFM experiments have reported a nearly-logarithmic increase in friction with increasing sliding speed, consistent with the behavior predicted by the PTT model in the thermal activation regime, for material pairs including Si on mica, 16 Si on gold, 14 Si on NaCl and highly ordered pyrolytic graphite (HOPG), 12,23,24 Si on HOPG, 25 Si on bulk and monolayer MoS2, 26,27 among others. Acikgoz et al have extended the work on the speed dependence of friction for the case of a Si tip sliding on exfoliated monolayer and bulk MoS2.…”
Section: Introductionsupporting
confidence: 71%
“…The PTT model represents, in a simplified way, the setup of an atomic force microscopy (AFM) experiment, in which a cantilever with a small tip having a radius typically on the order of tens of nanometers is pulled across a periodic crystal surface. Many AFM experiments have reported a nearly-logarithmic increase in friction with increasing sliding speed, consistent with the behavior predicted by the PTT model in the thermal activation regime, for material pairs including Si on mica, 16 Si on gold, 14 Si on NaCl and highly ordered pyrolytic graphite (HOPG), 12,23,24 Si on HOPG, 25 Si on bulk and monolayer MoS2, 26,27 among others. Acikgoz et al have extended the work on the speed dependence of friction for the case of a Si tip sliding on exfoliated monolayer and bulk MoS2.…”
Section: Introductionsupporting
confidence: 71%
“…In addition to theoretical and computational work aimed at elucidating the physical reasons behind the lubricative properties of layered materials [133][134][135], there have also been experimental studies that directly probe the underlying mechanisms with high spatial resolution. In addition to electron microscopy studies that manipulated individual sheets of layered materials in a controlled way while measuring the related forces during sliding [136,137], atomic force microscopy (AFM) experiments performed on single-or few-layer samples of graphene and MoS2 have revealed intriguing tribological characteristics on the nanometer length-scale, including but not limited to, layer- [138], speed- [139] and directiondependence (anisotropy) [140][141][142]. AFM has also been used to investigate friction mechanisms for other TMDs, including WS2 and WSe2 [143] as well as MoSe2 and MoTe2 [144].…”
Section: Solid Lubrication With 2d Layered Materialsmentioning
confidence: 99%
“…Also, an increase in the thickness of MoS2 results in the decrease of the nanofriction, and the increase in the anisotropy ratio of nanofriction. Ackgoz and co-workers [99] studied the influence of sliding speed on the frictional behavior of single-layer and bulk MoS2 using AFM experiments. They concluded that friction forces increase logarithmically with the increase in sliding speed.…”
Section: Molybdenum Disulfide (Mos2)mentioning
confidence: 99%